Molecular detection of avian spirochete Borrelia anserina in Argas persicus ticks in Algeria. (February 2020) - Ouchene, Nassim; Nebbak, Amira; Ouchene-Khelifi, Nadjet Amina; Dahmani, Ali; Zeroual, Fayçal; Khelef, Djamel; Bitam, Idir; Benakhla, Ahmed; Parola, Philippe
Graphical abstract: Highlights: The present study aimed to investigate the presence of avian spirochete Borrelia anserina in Argas persicus soft ticks in Algeria. A. persicus is the main soft tick in laying hens which is common mainly in summer. A total of 2/34 (5.88 %) A. persicus soft ticks were harbored Borrelia anserina . This result constitutes the first report in Algeria of A. persicus harboring B. anserina . Abstract: Argasid ticks are one of the most important poultry ectoparasites. They affect poultry directly through blood meal and indirectly through the transmission of pathogens essentially Borrelia anserina, agent of avian borreliosis, one of the most widespread poultry diseases in the world, and is of great economic importance. This study was conducted between April 2014 and March 2015 in the region of Ksar El Boukhari, Algeria, in order to investigate the presence of soft ticks in laying hen farms and to detect B. anserina bacteria using molecular tools. DNA was extracted and screened for the presence of Borrelia spp. DNA by real-time polymerase chain reaction (qPCR). Borrelia spp. screening was performed using primers and probe targeting the 16S rRNA gene. A total of 83 traditional laying hen farms were visited, of which 39 (46.98 %) were found infested with A. persicus tick. Molecular analysis revealed that 2/34 (5.88 %) of ticks were infected by B. anserina . None of the ticks tested were positive for Rickettsia spp., and Coxiella burnetii . These results constitute the first report in Algeria of A. persicus harboring B. anserina .